Historical Pathways for Opioid Addiction, Withdrawal with Traditional and Alternative Treatment Options with Ketamine, Cannabinoids, and Noribogaine: A Narrative Review - Amber N. Edinoff; Natalie W. Wu; Catherine A. Nix; Bryce Bonin; Rama Mouhaffel; Stephen Vining; William Gibson; Elyse M. Cornett; Kevin S. Murnane; Adam M. Kaye; Alan D. Kaye (Health Psychology Research, 2022)
Even as prescription opioid dispensing rates have begun to decrease, the use of illicit opioids such as heroin and fentanyl has increased. Thus, the end of the opioid epidemic is not in sight, and treating patients that are addicted to opioids remains of utmost importance. Currently, the primary pharmacotherapies used to treat opioid addiction over the long term are the opioid antagonist naltrexone, the partial-agonist buprenorphine, and the full agonist methadone. Naloxone is an antagonist used to rapidly reverse opioid overdose. While these treatments are well-established and used regularly, the gravity of the opioid epidemic necessitates that all possible avenues of treatment be explored. Therefore, in this narrative review, we analyze current literature regarding use of the alternative medications ketamine, noribogaine, and cannabinoids in treating patients suffering from opioid use disorder. Beyond its use as an anesthetic, ketamine has been shown to have many applications in several medical specialties. Of particular interest to the subject at hand, ketamine is promising in treating individuals addicted to opioids, alcohol, and cocaine. Therapeutically administered cannabinoids have been proposed for the treatment of multiple illnesses. These include, but are not limited to epilepsy, Parkinson's disease, multiple sclerosis, chronic pain conditions, anxiety disorders, and addiction. The cannabinoid dronabinol has been seen to have varying effects. High doses appear to reduce withdrawal symptoms but this comes at the expense of increased adverse side effects such as sedation and tachycardia. Noribogaine is a weak MOR antagonist and relatively potent KOR agonist, which may explain the clinical anti-addictive effects. More research should be done to assess the viability of these medications for the treatment of OUD and withdrawal.